Equations to estimate the total height of commercial culms in three bamboo species - Ordóñez Prado, Casimiro; Nava Nava, Adan; Juan Carlos,; Hernández Zaragoza, Pedro (Ecosistemas y Recursos Agropecuarios, 2023)
The total height (Th) of the culms is essential to carry out forest inventories of volume, biomass, carbon stores, and the distribution of products in bamboo stands. The high density of the canopy and the natural inclination of the upper part of the crown make its direct measurement of the field difficult. Allometric equations are a viable alternative to efficiently estimating the height as a function of the diameter at breast height (Dbh). The aim was to evaluate the quality of fit of Th-Dbh mathematical models and select the best predictive capacity to estimate the Th of culms of Bambusa oldhamii Munro, Guadua aculeata Rupr. and Guadua angustifolia Kunth in the Northeastern Sierra of Puebla, Mexico. In the analysis, 101 pairs of Th-Dbh observations were used, with which six allometric models and three growth models were fitted by non-linear regression. Nonlinear ordinary least squares techniques with indicator variables (NL-OLS-VI) and nonlinear mixed effects models (NL-MEM) were compared. The "nlme" package of the R software was used. We evaluated the models based on the adjusted coefficient of determination (R2adj), the root mean square error (RMSE), and the mean bias (B). NL-OLS-VI explained 83.5 % and NL-MEM 83.2 % of the observed variability. The model with the best performance was the Logistic fitted with NL-OLS-VI (R2adj = 0.835, RMSE= 2.280 m y B= 0.005 m). The generated Th- Dbh model is workable to estimate the Th for culms of the three bamboo taxa with low errors.
Keywords: random effects, prediction error, nonlinear functions, giant bamboo, allometric relationships